Competing water uses between agriculture and energy: Quantifying the future impacts of climate change for the Portuguese power sector - Fortes, Patricia (2022)
ABSTRACT: This paper analyses to which extent the competition for water resources between water demand for agriculture and hydropower may affect the future Portuguese carbon-neutral power sector under RCP8.5 climate scenario. Climate change effects on the availability of wind, solar PV and electricity demand are also modelled by the energy system eTIMES_PT model. Results show that, by 2050, Portuguese irrigation water demand is projected to increase between 3.5%-9.7% and 19% in Douro watershed, responsible for more than 50% of the national hydropower production. Consequently, annual average hydropower capacity factor reduces around 9-10%. Comparing with historical average hydrological years, climate change can lead to a reduction of hydropower production between -9% to -30%, which may be aggravated to -21% to -39%, with water competition. This reduction is compensated with a rise of Offshore Wind less affected by climate change.